2008
DOI: 10.1111/j.1540-8167.2008.01101.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Outcome Following Successful Pulmonary Vein Isolation: Pattern and Prediction of Very Late Recurrence

Abstract: Although most patients following PVI remain AF-free, some patients develop "late" recurrence of AF. The "late" recurrence patients are more likely to have hypertension and hyperlipidemia. Most late recurrences are associated with PV reconnections. Our observations emphasize the importance of continued long-term vigilance for AF recurrence, and also raise concerns regarding the need for long-term anticoagulation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
154
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(166 citation statements)
references
References 27 publications
7
154
1
4
Order By: Relevance
“…268,282,283,284,285,286,287,288,289,290,291,292,293,294,295,296,297,298 A recent meta-analysis identified 16 studies involving 5864 individuals reporting on the link between obesity and recurrence of AF after catheter ablation, identifying that there was a 3.1% greater risk of recurrent AF postablation for every one unit increase in BMI (RR 1.03; 95% CI 1.00–1.07). 299 …”
Section: Section 3: Modifiable Risk Factors For Af and Impact On Ablamentioning
confidence: 99%
“…268,282,283,284,285,286,287,288,289,290,291,292,293,294,295,296,297,298 A recent meta-analysis identified 16 studies involving 5864 individuals reporting on the link between obesity and recurrence of AF after catheter ablation, identifying that there was a 3.1% greater risk of recurrent AF postablation for every one unit increase in BMI (RR 1.03; 95% CI 1.00–1.07). 299 …”
Section: Section 3: Modifiable Risk Factors For Af and Impact On Ablamentioning
confidence: 99%
“…Many factors (type of AF, LA size, age, sleep apnea and obesity, hypertension, LA fibrosis detected by magnetic resonance imaging, diabetes, a rise in right atrium magnetic strength) have been proposed as predictors of a poorer outcome after PVI [18,19] but the discrepancies among authors [20][21][22][23][24][25] showed the complicated nature of already ablated atrial tissue. We applied a combined ALARMEc risk score which effectively discriminates patient outcome after any ablation procedure [4,5].…”
Section: Alarmec Risk Score and Long-term Successmentioning
confidence: 99%
“…22,25 However, as documented by Shah and colleagues, late AF recurrences can occur, even after several years of apparent freedom from AF following ablation. 9 Thus, the optimal anticoagulation strategy following AF ablation needs to be tailored to the individual risks and preferences of the patient. Three series have examined the safety of discontinuing warfarin following AF ablation.…”
Section: Figurementioning
confidence: 99%
“…6 Studies using prolonged external monitoring after AF ablation have found a significant incidence of asymptomatic AF after ablation, and recent studies have shown that late recurrences of AF can continue to occur even five years after the initial ablation procedure. [7][8][9] The guidelines state that discontinuation of warfarin should be based on the patients CHADS 2 score rather than freedom from AF recurrence. 2,10 Importantly, two recent multicenter reviews from Cappato and colleagues have described a 6% incidence of major complications from AF ablation, including a 1/1000 risk of death.…”
Section: Introductionmentioning
confidence: 99%